Role of GALNT14 in lung metastasis of breast cancer - Kim, Mi-Young (BMB Rep, 2017)
Aberrant expression of the polypeptide N-acetyl-galactosaminyltransferase (GALNTs) has been associated with cancer, but their function(s) in metastasis remains elusive. We have recently identified GALNT14, one of the O-GalNAc glycosylation-initiating enzymes, as a prognostic marker for pulmonary relapse in breast cancer patients. Furthermore, we showed that GALNT14 promotes lung metastasis by the following novel mechanisms: 1) enhancing metastasis initiation by inhibiting the anti-metastatic effect of BMP produced from the lung stroma, 2) exploiting growth signals (e.g. FGF) supplied by macrophages, for their growth into macrometastases in the lung environment. These multi-faceted roles of GALNT14 in lung metastasis are achieved by GALNT14-mediated inhibition and activation of the BMP and FGF signaling pathways, respectively. The link among GALNT14, its downstream pathways and lung metastasis, provides us with an opportunity to develop effective therapeutic intervention for breast cancer.